Analysis of Planning to Enhance Creativity Using Appropriate Media and Learning Models for High School Students - Wulandari, Puja Tri; Sumah, Astrid Sri Wahyuni (Jurnal Pijar Mipa, 2024)
Improving the quality of education is sought in the teaching and learning process. Learning is a process that impacts teachers and students in teaching and learning activities by increasing interest in material that is considered problematic. Media and learning models that can foster students' sense of creativity play an essential role in overcoming obstacles to understanding subject matter that students consider difficult. So, this research aims to discover the types of media and learning models that are supposed to increase the creativity of Class X students at SMA PGRI 1 Palembang. The method used is a method with a descriptive research design and data collection using questionnaires, interviews, and observations during learning. The results show that students need learning media that is often related to their daily lives, namely social media. The social media that is most owned by students and is considered to be able to act as additional media in learning is Instagram. Students chose this social media platform because it can foster students' sense of creativity in creating work that helps them understand complicated subject matter. These students' opinions support selecting the PjBL model as the learning model biology students and teachers need. This is because combining media and learning models suitable for use in the classroom provides opportunities to increase students' creativity in finding ways to understand the subject matter independently.